New Spectrophotometric and Conductometric Methods for Macrolide Antibiotics Determination in Pure and Pharmaceutical Dosage Forms Using Rose Bengal - Rania A. Sayed; Wafaa S. Hassan; Magda Y. El-Mammli; Abadalla Shalaby (Journal of Spectroscopy)
Two Simple, accurate, precise, and rapid spectrophotometric and conductometric methods were developed for the estimation of erythromycin thiocyanate (I), clarithromycin (II), and azithromycin dihydrate (III) in both pure and pharmaceutical dosage forms. The spectrophotometric procedure depends on the reaction of rose bengal and copper with the cited drugs to form stable ternary complexes which are extractable with methylene chloride, and the absorbances were measured at 558, 557, and 560 nm for (I), (II), and (III), respectively. The conductometric method depends on the formation of an ion-pair complex between the studied drug and rose bengal. For the spectrophotometric method, Beer's law was obeyed. The correlation coefficient () for the studied drugs was found to be 0.9999. The molar absorptivity (), Sandell’s sensitivity, limit of detection (LOD), and limit of quantification (LOQ) were also calculated. The proposed methods were successfully applied for the determination of certain pharmaceutical dosage forms containing the studied drugs